Virtual scale endoscope versus snares for accuracy of size measurement of smaller colorectal polyps: a randomized controlled trial - Djinbachian, Roupen; Taghiakbari, Mahsa; Alj, Abla; Medawar, Edgard; Sidani, Sacha; Liu Chen Kiow, Jeremy; Panzini, Benoit; Bouin, Mickael; von Renteln, Daniel (Endoscopy, 2025)
Accurate measurement of polyp size during colonoscopy is crucial for informing clinical decisions such as resection technique and surveillance scheduling. This study aimed to compare the accuracy of polyp size measurement when using a virtual scale endoscope (VSE) or snare-based polyp size measurement.This randomized controlled trial enrolled 221 patients undergoing screening, surveillance, or diagnostic outpatient colonoscopies. Study subjects were randomized to have polyps detected during the colonoscopy measured for size either using the VSE or a snare of known size to estimate the size of each polyp. All polyps were measured for reference size directly after their removal from the colon using a digital caliper and before formalin fixation.93 polyps were included in the VSE group and 102 in the snare group. The VSE demonstrated significantly higher relative accuracy (80.0% [95%CI 77.0%–82.9%]) compared with snare-based size estimation (66.4% [95%CI 62.4%–70.5%]; P < 0.001). Misclassification rates were lower with the VSE for polyps >2 mm (13.1% vs. 39.3%) and >3 mm (22.6% vs. 55.4%). For diminutive polyps, the VSE better prevented misclassification of >5 mm polyps as 1–5 mm (21.4% vs. 73.0%). The VSE also outperformed snare-based estimation in measuring within 10% of the reference standard size (30.1% vs. 18.6%) and had lower rates of size underestimation (36.5% vs. 65.7%).Using the VSE improves the accuracy of polyp size measurement during colonoscopy in comparison with snare-based size estimation. In clinical scenarios, the VSE reduced misclassifications at clinically relevant size thresholds 2, 3, and 5 mm, which is relevant for the correct choice of polypectomy technique or when implementing resect-and-discard strategies.